The role of electronic machines in translation - Atif Abdullah Farhadi; Prof. Dr. Abdullah Hussein Rasool Rasool (Zanco Journal of Humanity Sciences)
Translation is one of the important ways to exchange views and information between different peoples and languages.  Since ancient times, peoples have resorted to translation to perform their business dealings, commercial treatment, understanding each other, and coexistence between them.